1990
DOI: 10.1007/bf02244235
|View full text |Cite
|
Sign up to set email alerts
|

Chronic morphine administration augments benzodiazepine binding and GABAA receptor function

Abstract: Behavioral and neurochemical evidence indicates links between the opioid and GABA neurotransmitter systems. To assess effects of chronic opiates on the major site of postsynaptic GABAergic activity, the GABAA receptor, we administered chronic morphine and naltrexone to mice and evaluated binding at the benzodiazepine and t-butylbicyclophosphorothionate (TBPS) sites and GABA-dependent chloride uptake. After morphine (3 days), benzodiazepine receptor binding in vivo but not in vitro was increased in cortex compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Hence, a parsimonious explanation for our results is that repeated activation of μ-opioid receptors (by exogenously administered DAMGO or by endogenous opioid peptide release elicited by sweetened-fat gorging) enacts either a direct change in GABA A receptor sensitivity per se, or a more general change in the balance of excitatory/inhibitory transmission such that the threshold for GABA-mediated inhibition is easier to achieve. Repeated opioid agonist (morphine) treatment produces certain effects in this direction, such as upregulation GABA A binding sites and muscimol-stimulated chloride uptake in synaptosomes (40), augmentation of GABA A δ-subunit expression in the Acb shell (41), and internalization of the GluR1 subunit of AMPA receptors in the Acb shell (42). Any of these mechanisms (or their combination) at the level of the Acb shell could conceivably produce hypersensitivity to muscimol-induced neural inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a parsimonious explanation for our results is that repeated activation of μ-opioid receptors (by exogenously administered DAMGO or by endogenous opioid peptide release elicited by sweetened-fat gorging) enacts either a direct change in GABA A receptor sensitivity per se, or a more general change in the balance of excitatory/inhibitory transmission such that the threshold for GABA-mediated inhibition is easier to achieve. Repeated opioid agonist (morphine) treatment produces certain effects in this direction, such as upregulation GABA A binding sites and muscimol-stimulated chloride uptake in synaptosomes (40), augmentation of GABA A δ-subunit expression in the Acb shell (41), and internalization of the GluR1 subunit of AMPA receptors in the Acb shell (42). Any of these mechanisms (or their combination) at the level of the Acb shell could conceivably produce hypersensitivity to muscimol-induced neural inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The greater dopamine release of diamorphine in the mesolimbic dopamine system (Devine et al, 1993) may also lead to less concomitant BZD use. It has been shown that chronic treatment with opiates alters BZD receptor binding and GABAA receptor function (Lopez et al, 1990;Sivam and Ho, 1982), and it is possible that various opiate ligands exert differential effects on the GABAA receptor. These neurobiological aspects will have to be examined in future experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if the anxiolytic actions of benzodiazepines relies on the release of endogenous opioids, this effect might be potentiated by virus-mediated overexpression of preproenkephalin. Additionally, chronic opioid treatment causes an alteration of GABA/benzodiazepine receptor numbers in the brain (Lopez et al 1990;Rocha et al 1993) suggesting potential changes in the GABA/BZ receptor could account for enhanced diazepam effects. Critically testing the involvement of such changes following gene transfer may be difficult due to the potentially small magnitude of effects limited to a confined brain area.…”
Section: Discussionmentioning
confidence: 99%